2018
DOI: 10.1158/1055-9965.epi-17-1083
|View full text |Cite
|
Sign up to set email alerts
|

Rural Disparities in Treatment-Related Financial Hardship and Adherence to Surveillance Colonoscopy in Diverse Colorectal Cancer Survivors

Abstract: Cancer survivors increasingly report financial hardship as a consequence of the high cost of cancer care, yet the financial experience of rural cancer survivors remains largely unstudied. The purpose of this study was to investigate potential rural disparities in the likelihood of financial hardship and nonadherence to surveillance colonoscopy. Individuals diagnosed with localized or regional colorectal cancer between 2004 and 2012 were ascertained by the population-based New Mexico Tumor Registry. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 32 publications
0
53
0
Order By: Relevance
“…Briant and colleagues showcased the benefits of using culturally tailored interventions to improve health awareness, knowledge, and behavior; their study showed that promotor(a)-led "home health parties" increased the use of fecal occult blood test screening from 51% to 80% among Hispanic men and women living in rural Washington State (10). McDougall and colleagues studied colorectal cancer survivors in New Mexico and found that those who lived in rural areas were more likely to experience financial hardship and less likely to adhere to recommended follow-up care, highlighting the importance that place plays in affordable, accessible survivorship care (11). To examine the associations of neighborhood characteristics in Missouri with treatment and outcomes of ductal carcinoma in situ, Zhang, Liu, and colleagues used census tract-level socioeconomic deprivation and rural-urban commuting area codes to define rurality; although differences in treatment, but not outcome, were found, the authors suggest that larger studies using nuanced definitions of rurality are needed to refine our understanding the contribution of place to outcome (12).…”
Section: Bridging the Gap: Stories From The Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Briant and colleagues showcased the benefits of using culturally tailored interventions to improve health awareness, knowledge, and behavior; their study showed that promotor(a)-led "home health parties" increased the use of fecal occult blood test screening from 51% to 80% among Hispanic men and women living in rural Washington State (10). McDougall and colleagues studied colorectal cancer survivors in New Mexico and found that those who lived in rural areas were more likely to experience financial hardship and less likely to adhere to recommended follow-up care, highlighting the importance that place plays in affordable, accessible survivorship care (11). To examine the associations of neighborhood characteristics in Missouri with treatment and outcomes of ductal carcinoma in situ, Zhang, Liu, and colleagues used census tract-level socioeconomic deprivation and rural-urban commuting area codes to define rurality; although differences in treatment, but not outcome, were found, the authors suggest that larger studies using nuanced definitions of rurality are needed to refine our understanding the contribution of place to outcome (12).…”
Section: Bridging the Gap: Stories From The Fieldmentioning
confidence: 99%
“…Although geography alone cannot predict cancer risk, it can impact prevention, screening, diagnosis, and treatment opportunities. The articles in this special CEBP Focus issue on rural cancer control explore geographic disparities across the cancer control continuum in several distinct rural communities and map out potential paths to reach geographic health equity (7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…A cancer diagnosis not only impacts an individual's physical and mental health, but may also significantly impact their financial well‐being . Studies have found that cancer survivors experience acute and/or chronic financial distress following their diagnosis, subsequent treatment, long‐term management of side effects, and continued follow‐up care . Specifically, survivors have a higher prevalence of: out‐of‐pocket medical costs, out‐of‐pocket costs as a percentage of income, employment loss, lost wages and reduced benefits, asset depletion and medical debt, difficulty paying for non‐medical bills, bankruptcy, financial worry, and overall financial hardship .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding financial distress among special populations of cancer survivors is important especially given the disparities of those residing in rural areas of the U.S . Compared to urban locales, rural communities commonly experience higher rates of cancer incidence and mortality, disparate socioeconomic and education outcomes, health insurance challenges, geographic isolation, transportation barriers, and difficulties accessing oncology and social services, among other issues, which may further exacerbate the financial hardship of being diagnosed with cancer . For example, McDougall et al found that rural colorectal cancer survivors in New Mexico were twice as likely as urban survivors to report treatment‐related financial hardship .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation